Brain structural and functional dissociated patterns in schizophrenia. Issue 1 (December 2017) - Zhuo, Chuanjun; Zhu, Jiajia; Wang, Chunli; Qu, Hongru; Ma, Xiaolei; Tian, Hongjun; Liu, Mei; Qin, Wen
Abstract Background Although previous studies found that aberrations in gray matter volume (GMV) and global functional connectivity density (gFCD) are important characteristics of schizophrenia, to the best of our knowledge no study to date has investigated the associations between the spatial distribution patterns of GMV and gFCD alterations. We investigated pattern changes in gFCD and GMV among patients with schizophrenia and their associated spatial distributions. Methods Ninety-five patients with schizophrenia and 93 matched healthy controls underwent structural and resting-state functional MRI scanning to assess gFCD and GMV. Results We found that gFCD increased in the subcortical regions (caudate, pallidum, putamen, and thalami) and limbic system (left hippocampus and parahippocampus), and decreased in the posterior parieto-occipito-temporal cortices (postcentral gyri, occipital cortex, temporo-occipital conjunction, and inferior parietal lobule), in patients with schizophrenia. By contrast, we found decreased GMV in brain regions including the frontal, parietal, temporal, occipital, cingulate cortices, and the insular, striatum, thalamus in these patients. Increased gFCD primarily occurred in subcortical regions including the basal ganglia and some regions of the limbic system. Decreased gFCD appeared primarily in the cortical regions. There were no statistically significant correlations between changes in gFCD and GMV, and their spatial distribution patterns, in different regions. Conclusions Our findings indicate that gFCD and GMV are both perturbed in multiple brain regions in schizophrenia. gFCD and GMV consistently decreased in the cortical regions, with the exception of the Supplementary Motor Area (SMA). However, in the sub-cortical regions, the alterations of gFCD and GMV showed the opposite pattern, with increased gFCD and decreased GMV simultaneously observed in these regions. Overall, our findings suggest that structural and functional alterations appear to contribute independently to the neurobiology of schizophrenia.